(untitled) (Medical Forum Monthly, 2022)
Objective: To assessed the perception of medical students regarding cost conscious practices in healthcare. Study Design: A Retrospective qualitative study Place and Duration of Study: This study was conducted at the Al-Tibri Medical College and Hospital, between the duration from September 2021 to October 2021 for a period of 03 months. Materials and Methods: An electronic survey was prepared and sent to total 460 participants out of which 145 were practicing physician and 315 were medical students of 4th and 5th year. This survey included 39 close- and open ended questions that was prepared after extensive literature review. Questions were asked in which respondents were requested to agree, disagree, or don’t know. Student’s responses were compared to practicing physician using Chi square test. Results: We observed from our data that practicing physician were comparably well aware about cost effective procedures than medical students. In our context the expert physicians were more likely to aware about cost reduction expenditure and electronic health records that can be effective way to reduce the cost on the other hand medical students were less aware about this strategy. Conclusion: The provision of resources that can be easily adopted by various institutions can help to speed the widespread adoption of HVC curriculum in medical schools. Moreover there is need to emphasize the curriculum to advance their knowledge against cost conscious care. Even with minimal clinical experience, medical students were able to identify instances of lack of attention to cost-conscious care as well as potential solutions.